Growth algorithms in the phonological networks of second language learners: A replication of Siew and Vitevitch (2020a) - Luef, Eva Maria (Journal of experimental psychology. General, 2022)
A recent study by Siew and Vitevitch (2020a) investigated word form lexica and their growth in children acquiring English and Dutch as first languages from a network perspective. They identified a unique developmental trajectory in network growth, with high-density neighborhoods becoming enriched through growth at early acquisition stages (the "preferential attachment" mechanism) but low-density neighborhoods gaining new neighbors at advanced acquisition stages (termed "inverse preferential attachment"). Their findings were confirmed for various languages, they fit with assumptions of cognitive efficiency in lexical memory and retrieval and are intriguing for second language research as well. The present study was designed as a replication of Siew and Vitevitch (2020a) study "An investigation of network growth principles in the phonological language network" with data of English-as-a-second-language learners. Results mirror findings by Siew and Vitevitch and demonstrate that preferential attachment is the main network growth algorithm driving lexical learning at early second-language proficiency stages, while inverse preferential attachment prevails at more advanced proficiency stages. The similar growth dynamics observed in phonological networks of first and second language users may indicate a universal cognitive principle underlying word learning. (PsycInfo Database Record (c) 2022 APA, all rights reserved).